2006
DOI: 10.1021/jf0614589
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Profiles of Red Clovers and Their Distribution in Different Parts Harvested at Different Growing Stages

Abstract: The isoflavone compositions and concentrations in the leaf, flower, petiole, and stem of 13 red clover cultivars were studied using high-performance liquid chromatography coupled with a diode array and a mass spectrometric detector with negative electrospray ionization. Different cultivars showed significantly different concentrations of individual and total isoflavones. The leaf contained the highest overall concentration, followed by the stem, petiole, and flower. Biochanin A and formononetin were the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
96
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 23 publications
19
96
1
Order By: Relevance
“…Similarly, there are no previous studies on phyto-oestrogens in chicory. The concentration of glycitein in red clover has been reported by Tsao et al (2006) who found similar levels as those found in this study. The concentration of glycitein in the other herbages and milk has not been reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, there are no previous studies on phyto-oestrogens in chicory. The concentration of glycitein in red clover has been reported by Tsao et al (2006) who found similar levels as those found in this study. The concentration of glycitein in the other herbages and milk has not been reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…Significant differences have been established among, but not within, red clover cultivars for the isoflavone concentration of various tissues (Francis and Quinlivan 1974;Tsao et al 2006). Although there is no research to date on the genetic variability of isoflavone concentrations in red clover, selecting and breeding cultivars to minimize or increase isoflavone concentrations appears to be an attainable objective (Rumball et al 2003(Rumball et al , 2005Papadopoulos and Tsao 2006).…”
Section: Mots Clésmentioning
confidence: 99%
“…Samples of four subterranean clovers and two red clovers containing isoflavone glycosides were enzymatically hydrolyzed with an improved b-glycosidase method [15]. Analytical methods have also been developed using HPLC combined with UV -ESI-MS for determination of isoflavone aglycones in T. pratense and related species (T. repens, T. hybridum, and T. campestre) [16], and for chemical profiling of isoflavones in red clover cultivars [17]. In another study, de Rijke et al [18] employed HPLC with photodiode array (PDA), fluorescence (FL), and APCI/ESI-MS detection for the analysis of extracts from the leaves of three Trifolium species.…”
Section: Introductionmentioning
confidence: 99%